Analysis of the Prisoner Students' Social Skills through Biology Learning on Utilizing Eggshell Waste Concepts: A Case Study at the School of the Children's Special Prison Institution Class II Bandung, Indonesia - Noviani Utami; Nuryani Rustaman; Bambang Supriyanto (Gagasan Pendidikan Indonesia, 2023)
This research aimed to investigate the social skills in the School of the Children's Special Prison Institution Class II Bandung, Indonesia. This study included six prison students in high school between the ages of 15 and 18. In two meetings, a case study was conducted using biology learning activities on the issue of using eggshell waste. Field notes and semi-structured interviews are used for collecting data. The collected data will be processed qualitatively through the data coding process, and the data reduction will be provided in a descriptive form in the data interpretation part. According to the findings, prison students have average social skills in the moderate group in the areas of communication and cooperative skills. The communication aspect of social skills is lower than the cooperation aspect. The revealed social skills are indicators of the development of the prison students at the in the School Children's Special Prison Institution Class II Bandung.